2015
DOI: 10.4103/2229-516x.165368
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid variant of urothelial carcinoma: Diagnostic challenges and role of immunohistochemistry

Abstract: Plasmacytoid carcinoma of the urinary bladder or plasmacytoid urothelial carcinoma (PUC) is rare and only recently described a histological variant of transitional cell carcinoma. The morphological resemblance of PUC to other malignancies is a source of diagnostic dilemmas and often misdiagnosis. Immunohistochemistry plays a pivotal role in narrowing the differential diagnosis and reaching to a conclusive diagnosis. A diagnosis of PUC usually carries a dismal prognosis. Hence, correct diagnosis is important. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Second, CD38 is an appropriate immunohistochemical marker for confirming a plasmacytoid transformation in a urothelial carcinoma. Several studies have shown that the plasmacytoid tumor cells of a urothelial carcinoma are immunoreactive for CD138 [ 3 – 6 ]. CD138 is a highly sensitive and specific marker for normal and neoplastic plasma cells [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, CD38 is an appropriate immunohistochemical marker for confirming a plasmacytoid transformation in a urothelial carcinoma. Several studies have shown that the plasmacytoid tumor cells of a urothelial carcinoma are immunoreactive for CD138 [ 3 – 6 ]. CD138 is a highly sensitive and specific marker for normal and neoplastic plasma cells [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plasmacytoid urothelial carcinoma, which is a characteristic morphology similar to plasma cells, is an unusual variant that is included in the World Health Organization classification of urothelial neoplasms [ 1 , 2 ]. Several studies have recently reported that the plasmacytoid component of a urothelial carcinoma exhibits positive staining for CD138, an immunohistochemical marker for plasma cells, in addition to showing a morphological similarity [ 3 – 6 ]. A plasmacytoid urothelial carcinoma is an aggressive subtype associated with a poor prognosis even if the plasmacytoid component is locally limited [ 7 ].…”
Section: Introductionmentioning
confidence: 99%